SOSIOLOGI LEMBAGA PENDIDIKAN: KELAS UNGGULAN SEBAGAI ARENA KONSTRUKSI DAN REPRODUKSI DIFERENSIASI SOSIAL SISWA DI MADRASAH TSANAWIYAH NEGERI 1 BANYUMAS - Lili Rahmawati; Muh.Hanif (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This article examines elite classes as arenas for the construction and reproduction of social differentiation among students at Madrasah Tsanawiyah Negeri 1 Banyumas through the perspective of the sociology of educational institutions. The main claim is that elite classes potentially create social differentiation by forming academic hierarchies, symbols of prestige, and social distance within the madrasah environment. Using a qualitative field research design with a case study approach, primary data were collected through observation, interviews with teachers, elite class students, non-elite students, and the school principal, as well as documentation of institutional policies. The findings confirm three dimensions of evidence: elite classes receive greater access to facilities and academic attention; the elite label constructs perceptions of superiority among students; and non-elite students experience feelings of inferiority and diminished academic self-confidence. The article argues that elite class systems function not merely as administrative tools for academic grouping, but as social mechanisms that reproduce stratification and inequality within Islamic educational institutions. Findings enrich discussions in the sociology of Islamic education in Indonesia and offer recommendations for more equitable institutional governance.